A stereo vision system for underwater vehicle-manipulator systems – proposal of a novel concept using pan-tilt-slide cameras. - Sagara, Shinichi; Ambar, Radzi; Takemura, Fumiaki (2013)
Underwater Vehicle-Manipulator Systems (UVMS) are expected to be used in various tasks in underwater environments. The manipulators of the UVMS are designed to execute tasks such as handling and catching objects. It is therefore necessary to equip UVMS with sensors that observe and measure the position of target objects. Stereo vision systems are one type of such sensors. We propose a stereo vision system for UVMS consisting of 2 mobile cameras that pan, tilt and slide individually using motors. This vision system is installed inside a waterproof cylindrical container that enables it to track a target object in underwater environments. Stereo vision system concept and mechanism are proposed, and the effectiveness of the proposed system is shown by experiments using a vision system prototype.